92.1k views
4 votes
Which expression is equivalent to the one shown below


√(36 * 3)

a \: \: 36 √(3)

b \: \:6 √(3)

c \: \: 6 * 3

d \: \: 36 * 3


User GBourke
by
5.2k points

2 Answers

0 votes

Answer: b

Step-by-step explanation: b

User Varun Nayyar
by
5.0k points
3 votes

Answer:

Option b: 6√3

Explanation:

Given expression is:


√(36*3)

We have to factorize the radicand in order to solve the given radical

So,


= √(3*3*2*2*3)

In order to solve the square root pairs are made:


=√(2^2 * 3^2 * 3)

To evaluate the square root, the exponents are multiplied by 1/2


= 2^{(2*(1)/(2))} *3^{(2*(1)/(2))} * 3^{((1)/(2))}\\=2*3*√(3) \\=6√(3)

Hence, option b is correct ..

User Dail
by
5.3k points